Gamification in tourism : designing memorable experiences - Bulencea, Paul, ....-; Egger, Paul, ....- (Norderstedt : Books on demand, 2015)
Tourists' expectations are increasingly complex and sophisticated. They are now seeking meaningful and more stimulating experiences from tourism providers. By combining Gamification with Experience Design the Gamification in Tourism book provides a comprehensive and novel approach on how to design such experiences. With its Memorable Experience Design framework and practical case studies the book should help tourism providers shift their thinking as to what they can offer in order to cater to the new needs of their guests.
Keywords: Experience Design; Gamification; Tourism -- Games